Links between energy access and food security in sub Saharan Africa: an exploratory review - Sola, P.; Ochieng, C.; Yila, Jummai Othniel; Iiyama, Miyuki (Springer, 2016)
Three quarters of the population in Sub Saharan Africa lacks access to modern energy, and relies instead on biomass fuels for cooking and heating. The environment and health implications of the use of biomass fuel has been widely documented in the literature, and has raised the topic of energy access in various policy and development arenas. Still, the impact of energy access on food security at the household level has not been explored in detail; consequently the two sectoral policies remain unaligned. Our aims for this review were to document how lack of access to energy can impact on food security through influence on dietary choices and cooking practices; and how reallocation of household resources from food to energy procurement causes a switch to biomass energy forms of lower grade. We searched the literature for published peer-reviewed articles available through major online publication databases, initially identifying 132 articles but finally reviewing a set of 19 that met our criteria. While most studies suggested that fuelwood scarcity can affect food security through three hypothesised pathways, very few of them provided empirical data to support this argument. Overall, the review found coping measures for woodfuel scarcity to be highly contextual and influenced by geography, household economy and labour availability. Due to the limited number of studies with detailed data, it was not possible to perform a comparative analysis that could support or refute a hypothesis that lack of access to energy can impact on food security. More rigorous studies on this topic are needed which could provide evidence for policy action.